Iso-stoichiometric fuel blends: characterisation of physicochemical properties for mixtures of gasoline, ethanol, methanol and water. (January 2015) - Pearson, Richard J; Turner, James WG; Bell, Arthur; de Goede, Stefan; Woolard, Chris; Davy, Martin H
When appropriately sourced, bioethanol and biodiesel fuels provide an opportunity for nations to increase their energy independence or to reduce greenhouse gas emissions by supplying energy-dense fuels which are miscible with fossil-derived gasoline and diesel. These fuels can be used in low concentrations in vehicles with no modifications; in the case of ethanol, only minor changes in the fuel system materials together with a low-cost alcohol sensor are necessary for compatibility with a high concentration. Ethanol provides the beneficial property of having a high research octane number which can be exploited at the high-load operating conditions in modern pressure-charged spark ignition engines. However, the availability of sustainable feedstocks constrains the supply of biofuels, and this limits the level at which they are able to displace fossil fuels. The miscibility of methanol with both ethanol and gasoline enables the penetration of alcohols in the fuel pool to be increased. The present work describes the properties of specific mixtures of gasoline, ethanol and methanol which are blended to be iso-stoichiometric and iso-energetic replacements for mixtures of gasoline and ethanol. A simple analytical approach to the formulation of these ternary blends is described on the basis of the volumetric energy density of the pre-blended components, and a number of further physicochemical properties are characterised, including their stoichiometries, vapour pressures, distillation characteristics and propensities to phase separate. Data on the octane numbers of the blends are reported. The properties of quaternary iso-stoichiometric blends of water, gasoline, ethanol and methanol (the so-called hydrous ternary blends) are also examined.